Investigating the Concept of “Lightness” As Reflected in the Russian-Speaking Ukrainians’ Linguistic Consciousness - Gordienko-Mytrofanova, Iia; Kobzieva, Iuliia; Borokh, Kateryna (Lesya Ukrainka Eastern European National University, 2020)
The purpose of this study is to define and describe the semantic components of the verbalised concept “lightness” as a component of ludic competence in the linguistic consciousness of the Russian-speaking people from Eastern Ukraine. The main method of the research was a psycholinguistic experiment. The sample comprised 426 young people (aged 18-35), males and females being equally represented. Cluster analysis showed that the core of the concept “lightness” is represented by three semantic groups: “the quality being light and insignificant in weight and size …”, “the feeling of happiness and joyful ease”, “the feeling of freedom …, cheerfulness, excitement”. The last two clusters reveal the ambivalent nature of the concept “lightness”. The concept “lightness” is characterized by a large variety of peripheral clusters. The ones that are especially noteworthy are “insight” and “duality”. The former reflects the cognitive component of lightness, which accounts for 3 per cent. The latter reflects the concept’s ambivalent nature. Basically, the semantic content of the core of the word “lightness” does not depend on gender. The comparative analysis of the concept “lightness” in the linguistic consciousness of Ukrainian citizens and people living in Russia reveals its nationally-specific perception in the linguistic consciousness of Ukrainian people, which was reflected in the most frequent reaction “freedom”. Taken together, both samples share a number of common features: wide semantic scope; strong synonymic and weak antonymic connections between stimulus and reactions; positive emotional response to the stimulus. Finally, the results of the free word association test with the stimulus word “lightness” were successfully used to define more precisely and expand our understanding of “lightness” as a component of ludic competence taking into account both core and peripheral clusters.
Keywords: ludic competence; playfulness; ludic position; lightness; psycholinguistic experiment; free word association test; linguistic consciousness